Association of HMGCR inhibition with rheumatoid arthritis: a Mendelian randomization and colocalization study - Ma, Li; Du, Yufei; Ma, Chao; Liu, Ming (Frontiers in Endocrinology, 2023)
The objective of this study was to investigate the association between Hydroxymethylglutaryl coenzyme A reductase (HMGCR) inhibition and rheumatoid arthritis (RA) using drug-target Mendelian randomization (MR) and genetic colocalization analyses.Methods: Two sets of genetic instruments were employed to proxy HMGCR inhibitors: expression quantitative trait loci (eQTLs) of target genes from the eQTLGen Consortium, and genetic variants associated with low-density lipoprotein cholesterol (LDL-C) levels with HMGCR locus from open genome-wide association studies (GWAS). Positive control analyses were conducted on type 2 diabetes and coronary heart disease, and multiple sensitivity analyses were performed.Results: Genetically proxied expression of eQTL was associated with a lower risk of RA (OR=0.996, 95% CI =0.992-0.999, P= 0.032). Similarly, Hydroxymethylglutaryl coenzyme A reductase (HMGCR) mediated low-density lipoprotein cholesterol was negatively associated with risk of RA (OR=0.995,95% CI =0.991-0.998, P= 0.007) in the inverse variance weighted (IVW) method. Colocalization analysis suggested a 74.6% posterior probability of sharing a causal variant within the SNPs locus (PH4=74.6%). A causal relationship also existed between HMGCR-mediated LDL and RA risk factors. The results were also confirmed by multiple sensitivity analyses.The results in positive control were consistent with the previous study.Our study suggested that HMGCR inhibition was associated with an increased risk of RA, while also highlighting an increased risk of current smoking and obesity. These findings contribute to a growing body of evidence regarding the adverse effects of HMGCR inhibition on RA risk, calling for further research on alternative approaches using HMGCR inhibitors in RA management.